2011
DOI: 10.1074/jbc.m111.249151
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Functional Analysis of Histidine Residues Essential for pH-dependent Multimerization of von Willebrand Factor

Abstract: von Willebrand factor (VWF) is a multimeric plasma protein that mediates platelet adhesion to sites of vascular injury. The hemostatic function of VWF depends upon the formation of disulfide-linked multimers, which requires the VWF propeptide (D1D2 domains) and adjacent DD3 domains. VWF multimer assembly occurs in the trans-Golgi at pH ϳ6.2 but not at pH 7.4, which suggests that protonation of one or more His residues (pK a ϳ6.0) mediates the pH dependence of multimerization. Alignment of 30 vertebrate VWF seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…The pH-dependent control of VWF multimerization in the N-terminal VWD1-D2-D′D3 domains depends on two conserved histidine residues of the VWD2 domain, His 395 and His 460 , respectively (12). Although the histidine residue His 395 is present in the VWD2 domain of MUC2, the second histidine residue His 460 is absent and may influence the different oligomeric state of these two structurally related proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH-dependent control of VWF multimerization in the N-terminal VWD1-D2-D′D3 domains depends on two conserved histidine residues of the VWD2 domain, His 395 and His 460 , respectively (12). Although the histidine residue His 395 is present in the VWD2 domain of MUC2, the second histidine residue His 460 is absent and may influence the different oligomeric state of these two structurally related proteins.…”
Section: Discussionmentioning
confidence: 99%
“…3D reconstructions based on transmission electron microscopy (TEM) images showed that the N-terminal VWF helix consists of 4.2 repeating units per turn (11). This pH-dependent packing required protonation of conserved histidine residues (12). Because the packing of VWF tubules depends solely on the N-terminal part of VWF, it was suggested that the rest of the VWF extended radially from the helix axis (11).…”
mentioning
confidence: 99%
“…More recent evidence suggests that protonation of one or more histidine residues in VWFpp mediates the pH dependence of multimerization. 31 By using histidine to alanine mutagenesis, Dang et al demonstrated that replacement of histidine 395 or 460 in VWFpp caused a profound defect in inter-subunit disulfide formation, suggesting that these 2 residues in VWFpp contribute to the pH-dependent regulation of VWF multimer assembly. 31 VWFpp clearly has a critical role in the multimerization of VWF.…”
Section: Life Cycle Of Vwf and Vwfppmentioning
confidence: 99%
“…Enabled by the lower pH of the Golgi apparatus, this intrinsic oxidoreductase function is activated by protonation of histidine residues adjacent to these CGLC sequences. 6 Mutations within these sequences inhibit multimerization but do not affect dimerization. Therefore, dimerization does not appear to be performed by an intrinsic oxidoreductase activity within VWF.…”
Section: Introductionmentioning
confidence: 99%